Gangrene and Perforation of the Gallbladder as a Complication of Typhoid Fever – A Case Report - Sarma, Arnabjyoti Deva; Das, Chinmoy; Sarma, Pratap Chandra (Scripta Medica, 2024)
A rare consequence of typhoid illness is gall bladder gangrene with perforation. The gut and more rarely, the gall bladder are involved in surgical complications of typhoid fever. The morbidity and fatality rates are high, especially if they are not discovered and treated in time. Case report of a male adolescent patient with gall bladder gangrene with perforation is presented. Despite the difficult care, cholecystectomy and early intervention had positive outcome.